Mathematical Problem Solving Ability in Auditory, Intellectually, Repetition Learning with Ethnomathematics Nuanced Viewed From Self-Efficacy - Tiara Medyasari, Larasati; Zaenuri, Zaenuri; Dewi, Nuriana Rachmani (Unnes Journal of Mathematics Education Research, 2021)
Mathematical problem solving ability is an important ability in learning mathematics. This study aims to describe students' mathematical problem solving abilities through AIR learning with ethnomathematics nuanced. This research is descriptive research. The population in this study were all class X of Senior High School 5 Semarang in the academic year 2019/2020. The sampling technique used was cluster random sampling. The sample in this study were X MIPA 10 as the experimental class and X MIPA 7 as the control class. The research subjects were selected based on self-efficacy categories, namely high, moderate, and low. The data collection techniques used were questionnaires and tests. The data analysis used was descriptive data analysis and independent sample t-test. The results showed that the application of the AIR learning model with ethnomatematics nuanced can improve students’ mathematical problem solving abilities. Students with high self-efficacy categories are able to achieve all four aspects of problem solving abilities, namely understanding problems, devising a plan, carrying the plan, and looking back correctly and completely, while students with moderate and low self-efficacy categories have not been able to achieve all four aspects of problem solving abilities.